MENGATASI MISKONSEPSI DINAMIKA DENGAN KONFLIK KOGNITIF MELALUI METODE DEMONSTRASI - Kurniadi, Erawan (Jurnal Pendidikan, 2008)
This research serves an analysis on showing and identifying the profile of students misconception on dynamics materials and its causes. The analysis is also set to measure to what extent is the students misconception able to be reduced by making use of cognitive conflict under demonstration method. The analysis results in conclusion that diagnostic test and interview catch dynamic misconception. Identified essential misconceptions belong to 7 profile types under causes which are limited by Newton Law, the wrong mathematic formulation for Newton Law. Cognitive learning by demonstration method can tentatively reduce the misconception. Misconceptions obtained before cognitive conflict by demonstration method are 91 % made by the students of Physics, and 60% made by students of mathematics. After cognitive conflict learning strategy, the misconceptions can be reduced to 36.5% and 14% repectiveJy.Key terms: misconception, cognitive conflict, demonstration.